Microsatellite based genetic diversity and mitochondrial DNA D-Loop variation in economically important goat breeds of Pakistan - Naqvi, A. N. (2017)
The present study was undertaken to analyze the genetic diversity of five economically important goat breeds of Pakistan, Beetal, Kaghani, Teddy, Nachi and Pahari. Fifteen microsatellite loci recommended by ISAG/FAO guidelines were investigated for measures of genetic variability, differentiation and population structure. The genetic variability in terms of allelic diversity and heterozygosity were moderate. The estimated inbreeding coefficient was low in all the investigated goat breeds and not significant. Overall, the populations were less diverse than Eurasian goat breeds, but did not exhibit signs of loss of diversity. Analysis of molecular variance (AMOVA) showed breed differences accounted for 5.42% of total genetic variation indicating low to moderate genetic differentiation among the investigated goat breeds. The genetic structure analysis revealed Teddy, Pahari, and Nachi as distinct breeds, while Beetal and Kaghani form a single genetic group distinct from the other three goats. The mitochondrial DNA control region sequences showed a total of 60 distinct haplotypes belonging to two major maternal lineages A and B1 with a frequency of 76.9% and 23.1% respectively. Comparison of mtDNA sequences from Pakistani, Indian and Iranian goats indicated distinct evolutionary history for Teddy, Beetal, Nachi and Pahari goats different from that of Indian and Iranian goats.